Design and evaluation of an UWB array antenna for detection and imaging system - Ahmed, Shaikh Faraz (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
Microwave detection and imaging systems have been of research interest for applications in the area of health, security, monitoring of structural damages, through-wall gap estimation and recognition of hidden metallic objects. This is needed particularly for relieving security concerns in populated public places such as airports, sports stadiums, mosques, and shopping malls. In this research is proposed one of such detection and imaging systems based on antenna with an associated feeding network. This research focuses on designing a compact-size, low-cost antenna with feeding network for enhanced system directivity and gain, making it capable of achieve reflection coefficient better than -10dB. Using CST software, Balanced Antipodal Vivaldi Antenna (BAVA) antenna element is simulated for parametric study of return loss, voltage standing wave ratio, electric and magnetic field, 3D far-field radiation and polar patterns. The resulting structure is made of two identical radiator edges, curving outward and downward with comb-shape slits tilting outward at 45o on both arms. Both radiators are fitted with circular slots of identical dimensional range etched as electromagnetic band-gap structured (EBG) symmetrical patterns, improving thus bandwidth and gain in consequence. The antenna is fabricated on a standard printed circuit board (PCB) using normal photolithographic process. A similar exercise is conducted for fabrication of Wilkinson Power Divider for mitigating signal loss on its way from source to antenna elements. The so designed antenna has been experimentally tested in two specially designed experimental setups: namely, using single antenna element for in between-walls gap estimation and a four-element array for cylindrical metallic objects detection. In the gap estimation experimental setup, 14 cm gap has been measured with 95.5% accuracy on-average. In the array-based experimental setup using Vector Network Analyzer (VNA) for detection of 2cm height and 2cm diameter metallic object behind the wall has been used. The reflection peaks associated with reflection from target object at 8.6ηs, 9.2ηs, and 9.5ηs are noted. The first peak is indicating outer 1cm thick cardboard wall refection, second peak due to inner reflection of cardboard wall, and the third peak is generated due to metallic object of measure dimensions. The process is repeated for defining the shape of target object, obtaining thus multiple successive readings saved and recorded in a comma separated values (CSV) file format as log data. Through time-domain plots and a tabulated data set, the log data is called in for processing by a purposely produce MATLAB code for generating the 2D image of target object.